Effects of Temperature on Wrist Flexor Muscles Endurance - Afsun Nodehi-Moghadam; Leila Rahnama; Maryam Habibi; Najafali Dehghani (Shiraz University of Medical Sciences, 2014)
Background: It is widely recognized that neuromuscular function is temperature sensitive. Changes in muscle temperature may affect muscle force development. The aim of this study was to investigate the effects of temperature on wrist flexor muscles endurance. Methods: Fifteen healthy subjects (mean age 21.13±1.30 years) participated in the present study. The wrist flexor muscles endurance was measured before and after applying ice and hot packs over the forearm for 15 minutes. Paired t tests were used to compare differences between pre and post intervention endurance. Results: The results showed a significant increase in wrist flexor muscles endurance after heating. (P=0.04). We also found that, cooling the forearm muscles leaded to significant decrease of wrist flexor muscles endurance (P=0.01). Conclusion: These results suggest that hand function is temperature sensitive. Therefore, further studies are needed to evaluate the effects of cold on muscular function in people working in workplaces with extreme temperature.